Solidification behavior and rheo-diecasting microstructure of A356 aluminum alloy prepared by self-inoculation method - Ming Li; Yuan-dong Li; Xiao-feng Huang (China Foundry, 2017)
Semisolid slurry of A356 aluminum alloy was prepared by self-inoculation method, and the microstructure and solidification behavior during rheo-diecasting process were investigated. The results indicate that the semisolid slurry of A356 aluminum alloy can be prepared by self-inoculation method at 600 °C. Primary α-Al particles with fine and spherical morphologies are uniformly distributed when the isothermal holding time of slurry is 3 min. Liquid phase segregation occurs during rheo-diecasting process of semisolid slurry and the primary particles (α1) show obvious plastic deformation in the area of high stress and low cooling rate. A small amount of dendrites resulting from the relatively low temperature of the shot chamber at the initial stage of secondary solidification are fragmented as they pass through the in-gate during the mould filling process. The amount of dendrite fragments decreases with the increase of filling distance. During the solidification process of the remaining liquid, the nucleation rate of secondary particles (α2) increases with the increase of cooling rate, and the content of Si in secondary particles (α2) are larger than primary particles (α1). With the increase of cooling rate, the content of Si in secondary particles (α2) gradually increases. The morphologies of eutectic Si in different parts of die casting are noticeably different. The low cooling rate in the first filling positions leads to coarse eutectic structures, while the high cooling rate in the post filling positions promotes small and compact eutectic structures.